The Evolution of Islamic Education Institutions in Indonesia - Defnaldi, Defnaldi; Yunani, Yunani; Warisno, Andi; Andari, An An; Anshori, M Afif (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Intriguing changes have been made to the evolution of Islamic education in Indonesia. The phase evolutions were chronologically studied in this article. Prior to independence, then through the Old Order regime, New Order regime, and reform eras. This is library research. This library research found Each period has had a unique and significantly influenced the development of Islamic education in Indonesia in terms of systems, management, and methodology, all the way up to the way Islamic education is envisioned.